2015
DOI: 10.1002/adma.201501692
|View full text |Cite
|
Sign up to set email alerts
|

3D WS2 Nanolayers@Heteroatom‐Doped Graphene Films as Hydrogen Evolution Catalyst Electrodes

Abstract: A 3D catalyst electrode is fabricated by layer‐by‐layer assembly of 2D WS2 nano­layers and P, N, O‐doped graphene sheets into a heterostructured film. The film exhibits remarkable hydrogen evolution performance, benefitting from the utmost exposed active centers on 2D nanolayers, highly expanded surface, and continuous conductive network, as well as strong synergistic effects between the components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
218
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(226 citation statements)
references
References 59 publications
4
218
0
Order By: Relevance
“…[121] Like other TMDs, ReS2 has shown 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 good HER performance -better than the more commonly used TMDs. [107,122] Gao et al [107] has tested HER on CVD grown ReS2@Au, and found that it exhibited ~ 200 mV less overpotential (η) than bare Au.…”
Section: Photocatalytic and Electrocatalytic Hydrogen Evolutionmentioning
confidence: 92%
“…[121] Like other TMDs, ReS2 has shown 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 good HER performance -better than the more commonly used TMDs. [107,122] Gao et al [107] has tested HER on CVD grown ReS2@Au, and found that it exhibited ~ 200 mV less overpotential (η) than bare Au.…”
Section: Photocatalytic and Electrocatalytic Hydrogen Evolutionmentioning
confidence: 92%
“…A common strategy to improve the conductivity of MX 2 electrolysts is modification with conductive carbon or metal. [137,146,147] Recent studies on integration of carbon materials such as carbon nanotubes, [148,149] carbon boxes [150] and reduced graphene oxide [43] with interlayerexpanded MoS 2 for improving HER performance are extensively investigated. For instance, Lan and co-workers employed a one-step hydrothermal method to synthesize MoS 2 /N-doped rGO nanocomposite with interlayer spacing of 0.95 nm as HER electrocatalyst.…”
Section: Applications As Electrocatalysts For Hydrogen Evolution Reacmentioning
confidence: 99%
“…4 In recent years, a wide variety of transition metals (Co, Ni, Fe, Mo and W) and derivative components have been selected as effective candidates. [5][6][7][8][9][10][11] Particularly, β-phase molybdenum carbides have been demonstrated as highly active HER catalysts, even though they are bulky particles, and their performances could be further improved by constructing proper nanostructures. [12][13][14][15][16][17] It was revealed that nanorods of β-Mo 2 C work better as an electrocatalyst for HER than bulk β-Mo 2 C. 12 In addition to the morphology contribution, hybridization with heteroatom-doped graphitic carbon could further improve its performance because the effective coupling between β-Mo 2 C and N-doped graphitic carbon can greatly modify the work function of the hybrid and thus reduce the proton adsorption and the reaction barrier.…”
Section: Introductionmentioning
confidence: 99%